High diversity of Escherichia coli causing invasive disease in neonates in Malawi poses challenges for O-antigen based vaccine approach - Oliver Pearse; Allan Zuza; Edith Tewesa; Patricia Siyabu; Alice J. Fraser; Jennifer Cornick; Kondwani Kawaza; Patrick Musicha; Nicholas R. Thomson; Nicholas A. Feasey; Eva Heinz (Communications Medicine)
Abstract Background Escherichia coli is an important cause of neonatal sepsis and the third most prevalent cause of neonatal infection in sub-Saharan Africa, often with negative outcomes. Development of maternally administered vaccines is under consideration, but to provide adequate protection, an understanding of serotypes causing invasive disease in this population is essential. We describe the genomic characteristics of a collection of neonatal E. coli isolates from a tertiary hospital in Blantyre, Malawi, with specific reference to potential protection by vaccines under development. Methods Neonatal blood or cerebrospinal fluid cultures from 2012 to 2021 identified 208 E. coli isolates, and 169 could be recovered for sequencing. Results Our data shows very high diversity in sequence types, LPS O-antigen-type and flagellar H-type, which all show temporal fluctuations and, as far as we are aware previously undescribed diversity, including ten putative novel O-types. Vaccines in clinical trials target the O-antigen but would only protect against less than half (37.9%) of neonatal sepsis cases in this population (EXPEC9V). An O-antigen-based vaccine would require 30 different O-types to protect against 80% of infections. Conclusions Vaccines against neonatal sepsis in Africa are of considerable potential value, but their development requires larger studies to establish the diversity and stability over time of relevant O-types for this population.